CALR-TLR4 Complex Inhibits Non-Small Cell Lung Cancer Progression by Regulating the Migration and Maturation of Dendritic Cells - Chen, Ruo; Huang, Min; Yang, Xu; Chen, Xiao-Hong; Shi, Ming-Yan; Li, Zhuo-Fan; Chen, Zhi-Nan; Wang, Ke (Frontiers in Oncology, 2021)
Background: Lung cancer is a common malignant tumor that threatens human life and is associated with high morbidity and mortality rates. Calreticulin (CALR) is a antigen characteristic of immunogenic cell death in non-small cell lung cancer (NSCLC), which is closely related to anti-tumor immunity, but its specific mechanism in anti-tumor immunity remains unclear. Methods: Immunohistochemical staining was performed to detect the expression of CALR and dendritic cell-lysosome-associated membrane glycoprotein (DC-LAMP) in NSCLC tissues. The cell supernatant was used to induce migration and maturation of dendritic cells (DCs). Western blot and real-time PCR were used to investigate the corresponding molecule expression in the CALR-Toll-like receptor 4 (TLR4)-MyD88 signaling pathway. Results: The expression of CALR on NSCLC cell membrane (mCALR) and DC infiltration in NSCLC were positively correlated and were closely related to the prognosis of NSCLC patients. Moreover, mCALR facilitated the migration and maturation of DCs by activating CALR-TLR4-MyD88 signaling and increasing the secretion of TNFα and CCL19, which was inhibited by the loss of TLR4. In vivo experiments demonstrated that mCALR inhibited lung cancer progression by facilitating DC infiltration in lung cancer tissues. Conclusion: Our study explores the function and mechanism of the CALR-TLR4 complex in DC migration and maturation and investigates the inhibitory effect of the CALR-TLR4 complex on lung cancer progression, providing a theoretical basis and ideas for immunotherapy of NSCLC.